Monandry (monogamy) in natural populations of anopheline mosquitoes. - V. Baimai (2018)
Polymorphic Y chromosomes within two species of anopheline mosquitoes provide markers for testing if females are inseminated by one or more males in nature. Wild-caught females of Anopheles dirus (sp. A) and An. maculatus s.s. produced 291 and 55 families, respectively, which showed a single type of Y chromosome. One family of the former species showed two types of Y chromosomes. These field data support the idea, established from laboratory studies, that female mosquitoes are largely monandrous (monogamous). Such information is important in interpretation of population biological data and, practically, in attempts to control insect pests by use of genetically designed males.